2017
DOI: 10.3389/fpsyg.2017.00339
|View full text |Cite
|
Sign up to set email alerts
|

Child Negative Emotionality and Parental Harsh Discipline in Chinese Preschoolers: The Different Mediating Roles of Maternal and Paternal Anxiety

Abstract: Previous research has suggested that harsh discipline is still prevalent in modern Chinese families and it is necessary to explore the cause and the potential mechanisms of Chinese parental use of harsh discipline. This study examined the mediating effects of parental anxiety in the relations between child negative emotionality and parental harsh discipline in China. Using a sample of 328 Chinese father-mother dyads with their young children, findings revealed that maternal anxiety mediated the relations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 62 publications
(67 reference statements)
3
14
0
Order By: Relevance
“…For the present study, Cronbach’s alphas for NA were .60 for the fathers and .59 for the mothers, and the Cronbach’s alphas for EC were .77 for the fathers and .80 for the mothers. These alphas are also consistent with those obtained in previous research (Laible, Panfile, & Augustine, 2013; Xing, Zhang, Shao, & Wang, 2017).…”
Section: Methodssupporting
confidence: 93%
“…For the present study, Cronbach’s alphas for NA were .60 for the fathers and .59 for the mothers, and the Cronbach’s alphas for EC were .77 for the fathers and .80 for the mothers. These alphas are also consistent with those obtained in previous research (Laible, Panfile, & Augustine, 2013; Xing, Zhang, Shao, & Wang, 2017).…”
Section: Methodssupporting
confidence: 93%
“…Results connecting parental anxiety and depressive problems and psychological maltreatment were supported by previous research (Xing et al., ). These results may be related to the strong connection between parental psychopathology and poor parenting strategies that result in hostile parenting behaviors like corporal punishment or verbal aggression (Lyons‐Ruth et al., ; Trepat et al., ; Walker & McKinney, ; Xing et al., ). Similarly, findings related to psychological maltreatment by parents were supported by previous literature.…”
Section: Discussionsupporting
confidence: 85%
“…Mothers with depression also were more likely to argue with their young children, be critical and hostile, and be inconsistent (Cummings, Keller, & Davies, ; Jaser et al., ). Similarly, Xing, Zhang, Shao, and Wang () found that maternal and paternal anxiety predicted child psychological maltreatment and corporal punishment in a sample of young children. Likely, parents with anxiety have less developed coping strategies and greater emotion dysregulation, which lead to parents getting frustrated with their children more easily (Kerns, Pincus, McLaughlin, & Comer, ).…”
Section: Odd Problems In Emerging Adulthood and Gendermentioning
confidence: 92%
“…Studies have variously described parenting styles in Asian culture as “authoritarian,” “strict” and “lacking in expressivity” as compared to authoritative parenting styles (e.g., high in support and moderate control) commonly seen in Western culture [6870]. In Asian cultures, parents often express their love for children by providing resources for their children’s physical needs or through sacrifices [69] and physical or corporal punishment which is often the common parental disciplinary technique in some traditional families [71, 72]. Parental expressivity such as acceptance and care in Asian culture are shown through “instrumental support” (e.g., clothing, food, schooling, etc.)…”
Section: Discussionmentioning
confidence: 99%